Modelling toxin effects on protein biosynthesis in eukaryotic cells. (August 2017) - Skakauskas, Vladas; Katauskis, Pranas
Graphical abstract: Highlights: Model for toxin inhibition of protein synthesis in eukaryotic cells is proposed. Model for mitigation of toxic effect with application of antibodies is studied. Effect of antibodies is estimated by the antibody protection measure. Abstract: We present a rather generic model for toxin (ricin) inhibition of protein biosynthesis in eukaryotic cells. We also study reduction of the ricin toxic effects with application of antibodies against the RTB subunit of ricin molecules. Both species initially are delivered extracellularly. The model accounts for the pinocytotic and receptor-mediated toxin endocytosis and the intact toxin exocytotic removal out of the cell. The model also includes the lysosomal toxin destruction, the intact toxin motion to the endoplasmic reticulum (ER) for separation of its molecules into the RTA and RTB subunits, and the RTA chain translocation into the cytosol. In the cytosol, one portion of the RTA undergoes degradation via the ERAD. The other its portion can inactivate ribosomes at a large rate. The model is based on a system of deterministic ODEs. The influence of the kinetic parameters on the protein concentration and antibody protection factor is studied in detail.